PLANNING SEISMIC NETWORKS FOR TSUNAMI PREDICTION - Omelchenko O.K.; Gusyakov V.K. (My University, 1996)
Specific problems in the design and analysis of seismic networks are considered and algorithms for their solution are discussed. Two problems are considered as examples: (1) seismic network analysis for the second phase of the Unified Automated Tsunami System (UATS) and (2) the order of putting seismic stations in operation. The former is solved by the methods of conventional regression analysis used to plot contour maps of the confidence intervals of hypocenter parameters, the latter is treated using optimal planning techniques by adding a varying number of stations to the basic triple VLA, PET, YSS.